2010
DOI: 10.1111/j.1465-7287.2009.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Soft Drink Taxes Reduce Population Weight?

Abstract: Soft drink consumption has been hypothesized as one of the major factors in the growing rates of obesity in the US. Nearly two-thirds of all states currently tax soft drinks using excise taxes, sales taxes, or special exemptions to food exemptions from sales taxes to reduce consumption of this product, raise revenue, and improve public health. In this paper, we evaluate the impact of changes in state soft drink taxes on body mass index (BMI), obesity, and overweight. Our results suggest that soft drink taxes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 45 publications
6
118
0
3
Order By: Relevance
“…Fletcher et al 41 analysed the relationship between soft drink taxes in states in the USA, which averaged 3%, and population BMI between 1990 and 2006 and found that even relatively large tax increases had little effect. Similarly, Oaks 43 found no relationship between obesity prevalence and a snack and soft drink tax of 5.5% in Maine, USA, on comparing the obesity rate over 15 years with that in New Hampshire, a state with no tax.…”
Section: Grey Literaturementioning
confidence: 99%
“…Fletcher et al 41 analysed the relationship between soft drink taxes in states in the USA, which averaged 3%, and population BMI between 1990 and 2006 and found that even relatively large tax increases had little effect. Similarly, Oaks 43 found no relationship between obesity prevalence and a snack and soft drink tax of 5.5% in Maine, USA, on comparing the obesity rate over 15 years with that in New Hampshire, a state with no tax.…”
Section: Grey Literaturementioning
confidence: 99%
“…The pool own-price elasticity was -1.299 (95% CI: -1.089 to -1.509), denoting that a 10% increase in a tax would reduce SSB consumption by 12.99%. With respect to the impact of taxes on obesity, studies conducted in the United States found that a 1% increase in SSB prices can reduce obesity prevalence in adults and children by 0.0001 (Fleetcher et al 2010) and 0.0090 (Fletcher et al 2010), respectively. Another study in the United States indicated that a 10% increase in SSB prices can reduce obesity prevalence in men and women by 0.05 and 0.34, respectively (Han and Powell 2011), while a third study indicated that a 20% increase in SSB prices can reduce obesity prevalence by 0.0300 (Smith et al 2010).…”
Section: Effectiveness Of Sugar-sweetened Beverage Taxesmentioning
confidence: 99%
“…Two such studies (22,23) , conducted in the USA, demonstrated the cost-effectiveness of this intervention. However, other estimates for the USA, where already two-thirds of the States apply some kind of specific taxation to SSB, are more pessimistic, reporting that although these taxes do reduce the BMI of the population, the change is minimal (24) .…”
Section: Taxation Possibly the Most Effective Levermentioning
confidence: 99%